In vitro micropropagation of pointed gourd (Trichosanthes dioica Roxb.) from shoot tip and nodal segment (Bangladesh Journal of Scientific and Industrial Research, 2012)
An efficient protocol was developed for plant regeneration, multiplication and rooting under in vitro condition in pointed gourd. Highest percent of shoot regeneration was 91.66%, when nodal explants were cultured on MS+1.0 mg/1 BAP. The maximum number of shoots (4.8) per explant was observed in MS + 1.0 mg/1 BAP + 0.2 mg/1 NAA from nodal segment. Among the two explants, nodal segment was found better for shoot regeneration and multiplication. The best response towards root induction was achieved on half MS medium supplemented with 0.4 mg/1 NAA. The regenerated healthy rooted plantlets were transferred to small plastic pot containing garden soil and compost in a ratio of 2:1. Immediately after transplantation the plantlets were covered with polythene bag to prevent desiccation. After acclimatization the plantlets were successfully transferred to the garden soil and the percentage of survivability in such condition was 90%.   DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11457   Bangladesh J. Sci. Ind. Res. 47(2), 217-222, 2012